2019
DOI: 10.1029/2018wr024174
|View full text |Cite
|
Sign up to set email alerts
|

Permeability Prediction in Rocks Experiencing Mineral Precipitation and Dissolution: A Numerical Study

Abstract: In this study, we focus on the electrical tortuosity‐based permeability model k = reff2/8F (reff is an effective pore size, and F is the formation factor) and analyze its applicability to rocks experiencing mineral precipitation and dissolution. Two limiting cases of advection‐dominated water‐rock reactions are simulated, that is, the reaction‐limited and transport‐limited cases. At the pore scale, the two precipitation/dissolution patterns are simulated with a geometrical model and a phenomenological model. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 89 publications
5
38
0
Order By: Relevance
“…By contrast, uniform mineral growth around the grains represents a surface reaction-controlled process [ 74 ], whereby the chemical reaction rate limits precipitation and the pore space is altered homogeneously. Both spatial precipitation patterns have been observed in several laboratory [ 19 , 21 , 56 ] and numerical studies [ 18 , 80 , 81 ], investigating mostly calcite and barite precipitation in porous media. Preferential precipitation in regions of LFV can be explained by an undisturbed growth of minerals, whereby fluid shear stresses limit precipitation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…By contrast, uniform mineral growth around the grains represents a surface reaction-controlled process [ 74 ], whereby the chemical reaction rate limits precipitation and the pore space is altered homogeneously. Both spatial precipitation patterns have been observed in several laboratory [ 19 , 21 , 56 ] and numerical studies [ 18 , 80 , 81 ], investigating mostly calcite and barite precipitation in porous media. Preferential precipitation in regions of LFV can be explained by an undisturbed growth of minerals, whereby fluid shear stresses limit precipitation.…”
Section: Discussionmentioning
confidence: 86%
“…These findings lie in the range of the simulated contrasting cases of a uniform mineral growth and preferential precipitation at high flow velocities, which demonstrates the applicability of the simulated reaction- and transport-controlled precipitation process applied in the present study. Niu and Zhang [ 80 ] even found a higher value of = 30, considering a transport-limited mineral growth and concluded that a constant exponent cannot describe this process sufficiently well due to the strong permeability decrease. The Kozeny–Carman relation initially exhibits a good agreement with a uniform mineral growth around the grains.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, it promotes a high pH environment, leading to dissolving minerals such as quartz, feldspar, and clays (Yupu et al, 2004). Several scholars have studied the formation of silicate scaling during water flood, confirming the possible reservoir damage caused by the precipitation of silica ions (Ikeda & Ueda, 2017;Niu & Zhang, 2019;Yanaze et al, 2019). A recent study by (Yanaze et al, 2019) reported a reduction in flow rates during water flooding accompanied by a significant reduction in permeability due to silica precipitation.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, reaction rates and the spatial distribution of reaction products should be relatively homogeneous over length scales that do not result in significant variations in temperature/kinetics (i.e., a few 10's or perhaps 100's of meters in the crust). Reaction-limited transport in both porous media and fracture networks in the crust has been inferred by a variety of experimental, numerical, and rockrecord studies [25][26][27][28][29][30][31][32] and may be particularly applicable during cementation of fracture networks when the rates of fluid advection are modest or where the precipitation reaction is kinetically limited. Thus, in a fractured but homogeneous rock mass or in a rock mass where mineralogical variations (and associated surface chemistry heterogeneities) occur over smaller spatial scales than those of fracture length, the rate of aperture decrease and fracture sealing during cementation should be approximately constant through space and time.…”
Section: Introductionmentioning
confidence: 99%